Propriedades físicas e infiltração de água de um Latossolo Vermelho Amarelo (Oxisol) do noroeste do estado de São Paulo, Brasil, sob três condições de uso e manejo - Alves, M. C. [UNESP] (2005)
This study presents the results obtained in a field experiment carried out at Glicério, Northwest of São Paulo state, Brazil, whose objective was to analyze changes of selected soil physical properties and water infiltration rates on a Yellow-Red Latosol, under three different management conditions. The experimental design was arranged as completely randomized split-block with twelve treatments, which corresponded to four depths (0-0.05 m; 0.05-0.10 m; 0.10-0.20 m and 0.20-0.40 m) and three conditions of soil use and management with four replications. The soil surface conditions were: conventional tillage (one disking with moulboard plus two levelling passes with harrow), nine months before starting filed experiences; recent conventional tillage (also one disking with moulboard plus two levelling passes with harrow) and native forest. The conventional tillage areas were cropped for about fifteen years with annual cultures. The considered soil general physical properties were: macroporosity, microporosity, total porosity, bulk density, soil moisture and penetration resistance and, in addition; soil water infiltration rates were also recorded. According to our results, differences on general soil physical properties and infiltration rates appeared when both tilled sub-treatments and native forest were compared. Both, plots recently prepared by conventional tillage and those prepared by tillage but left nine months in rest, presented a statistically significant decrease of constant (final) water infiltration rates of 92.72% and 91.91% when compared with native forest plots.